The battle of the ancient economy - Hindess, Barry (Economy & Society, 2007)
Ancient Athens and Modern Ideology addresses the battle between primitivism and modernism over the ancient economy, focusing especially on the contributions of three major figures, Max Weber, Karl Polanyi and Moses Finley. Finally, a short Epilogue returns to the examination of Marx's puzzle and his manifestly unsuccessful attempt to resolve it. Mohammad Nafissi uses this discussion to put this dispute out of its misery by advancing his own resolution of the primitivist-modernist dispute. Unfortunately, the limitations he seeks to avoid are mostly those which the supporters of one or the other side have identified in the claims of their opponents. As a result, his attempted resolution fails to disrupt their shared assumptions regarding the special place of the ancient Greeks in human development.
Political Science; Sociology
Keywords: Athens (Greece); FINLEY; M. I. (Moses Israel); 1912-1986; Greeks; WEBER; Max; 1864-1920; book review; history of economics; ideology; primitivism; socioeconomics